Effect of a moisturizing/antiseptic solution of guar gum in tea tree oil in the periorbital region of domestic dogs (Research, Society and Development, 2023)
Conjunctivitis cleaners used to remove periorbital cleaners used to remove and remove cleaning products. Usually, chemically modified products are used, seeking their local preference or animal rejection. One of the limiting factors is odor, as this sense is very sharp in dogs. Natural component products are more easily handled by animals and more easily acted upon by natural, microbial and parasitic reduction eye products. We determined the tolerance of domestic animals to a solution of guar gum in tea tree oil, compounded with wide use in humans and animals, with documented safety. We applied the 1% tea tree guar gum solution (Eyepet®) in 30 randomly selected animals, under the supervision of their tutors. All animals had excellent tolerability, without any sign of good local tolerance or systemic toxicity. Although the common sense solution indicated that a solution of guar-melaleuca gum would be well tolerated, our results are relevant to guarantee the safety of the use of this common one for the periorbital asepsis of dogs.